2009
DOI: 10.2298/ciceq0904203g
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles of activated natural zeolite on textiles for protection and therapy

Abstract: Activated natural zeolite clinoptilolite is microporous hydrated aluminosilicates crystals with well-defined structures containing AlO 4 and SiO 4 tetrahedral linked through the common oxygen atoms. It is to point out that zeolites act as strong adsorbents and ion-exchangers but having many other useful properties. Due to its cationexchange ability, zeolites have catalytic properties and, for that, multiple uses in medicine and industry, agriculture, water purification and detergents. Zeolites are nontoxic sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 11 publications
(17 reference statements)
5
26
0
1
Order By: Relevance
“…As can be seen from the curves, zeolites significantly enhanced the absorption ability of UV-rays (reflectance values are lower in comparison to the reference sample). The stronger the UV absorption intensity of the zeolite-modified textiles, the higher the UV protection ability was; which is in good agreement with the UPF results disclosed additionally in Figure 7, as well as with the findings of the study accomplished by [16]. besides the above-mentioned, as could be perceived from Figure 5b, at 1708 cm −1 and 1239 cm −1 on account of the carbonyl stretching and N-H vibrations of -CO-NH-R bonds [27], which were formed as a result of successful high-temperature crosslinking between adjacent cellulose chains and the mDMDHEU.…”
Section: Diffuse Reflectance Spectra Profile Determination and Cie Mesupporting
confidence: 91%
See 2 more Smart Citations
“…As can be seen from the curves, zeolites significantly enhanced the absorption ability of UV-rays (reflectance values are lower in comparison to the reference sample). The stronger the UV absorption intensity of the zeolite-modified textiles, the higher the UV protection ability was; which is in good agreement with the UPF results disclosed additionally in Figure 7, as well as with the findings of the study accomplished by [16]. besides the above-mentioned, as could be perceived from Figure 5b, at 1708 cm −1 and 1239 cm −1 on account of the carbonyl stretching and N-H vibrations of -CO-NH-R bonds [27], which were formed as a result of successful high-temperature crosslinking between adjacent cellulose chains and the mDMDHEU.…”
Section: Diffuse Reflectance Spectra Profile Determination and Cie Mesupporting
confidence: 91%
“…It was evident from Figure 8 that the untreated cotton had UPF 3.4, indicating a non-ratable UV protection level. After the applications of 5 and 30 g/L of zeolite particles during the pad-drythermofix procedure, the fabric UPFs increased exceedingly, as expected from the literature [16], i.e., up to values of 24.4 (30 g/L Z at pH 11), and 27.3 (30 g/L Z@mDMDHEU at pH 11), meaning good to very good UV protective properties with regard to ASTM guidelines for labelling UV-protective clothing (ASTM D 6603), which was in good agreement with the above-presented DRS profiles in the UV region (Figure 6). Although the achieved UPFs of all the zeolite-modified/washed samples were lower than the value of 55 declared as excellent protection (UPF 50+), the gained results confirmed that zeolites impart functionality to cellulose fabrics against the transmittance of harmful solar UV rays.…”
Section: Uv-protective Propertiessupporting
confidence: 82%
See 1 more Smart Citation
“…Zeolites are a group of aluminosilicates that exhibit diverse biological activities and have found uses as adjuvant therapy in anticancer therapy, adjuvant for vaccines, treatment of heartburn, and as antidiarrheal agents [8][9][10][11][12][13][14][15][16][17] . Natural zeolites are hydrated porous volcanic microcrystals formed mainly of AlO 4 and SiO 4 , which have defined shapes resulting from tetrahedral building blocks connected through O 2 atoms.…”
Section: Introductionmentioning
confidence: 99%
“…of fibre, fabric surface and construction, type and concentration of dyestuff, fluorescent whitening agent (FWA), UV-B protective agents, as well as nanoparticles, if applied [6,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
mentioning
confidence: 99%